Metabolomics study of renal fibrosis and intervention effects of total aglycone extracts of Scutellaria baicalensis in unilateral ureteral obstruction rats. (4th November 2016) - Fang, Junwei; Wang, Wenyu; Sun, Shujun; Wang, Yang; Li, Qianhua; Lu, Xiong; Qiu, Mingfeng; Zhang, Yongyu
Abstract: Ethnopharmacological relevance: Scutellariae Radix ( Scutellaria baicalensis Georgi ) is a well-known Traditional Chinese Medicine (TCM) which mainly contains flavonoids. Our previous studies have demonstrated that total aglycone extracts of Scutellaria baicalensis (TAES) can improve kidney disease in rats. Aim of the study: To investigate the renal fibrosis (RF) pathogenesis and TAES treatment mechanism in unilateral ureteral obstruction (UUO) rats, using a metabolomics approach based on gas chromatography-mass spectrometry (GC/MS). Methods: Rats with RF were divided into 6 groups with rats subjected to sham operation as normal control. The effects of TAES on some RF closely related parameters in UUO rats were investigated. A metabolomics method, based on GC/MS, was developed to monitor metabolic alterations in urine. Multivariate data analysis was utilized to identify biomarkers potentially associated with RF and the anti-RF activity of TAES. Ontology-based enrichment analysis by BiNChE and pathway analysis by MetPA aid in the interpretation of difference metabolites. Results: After 10 days of treatment, the parameters of renal function begin returning to normal, and the abnormal high expressions of genes associated with extracellular matrix (ECM) were relived. In the metabolomics study, metabolic perturbations induced by UUO were reversed after treatment and TAES showed a dose-dependent therapy effect on RF, meanwhile, 18 potential biomarkers associated with RF were identified. Enrichment analysis of metabolites shows an over representation of mostly alkane-alpha, omega-diamine and alpha, omega-dicarboxylic acid, and these biomarkers are primarily involved in Glycine, serine and threonine metabolism, Retinol metabolism, Arginine and proline metabolism and Fructose and mannose metabolism. Conclusions: Our findings indicate that TAES have positive effects on UUO-induced RF in rats, meanwhile, metabolomics method coupled with metabolites enrichment analysis is a useful tool for revealing the pathogenesis of diseases and action mechanism of TCM on the whole body. Graphical abstract: